Risks and Benefits of Device-Assisted Treatment of Pulmonary Embolism - Kim, Sofia; Kim, Michael; Kodra, Arber (International Journal of Angiology, 2024)
Pulmonary embolism (PE) is a common disease associated with significant morbidity and mortality. Despite the familiarity with this disease, the best treatment remains undefined. Traditionally, treatment of PE has involved a choice of anticoagulation, thrombolysis, or surgery. However, the debate over pharmacologic versus mechanical treatment of acute PE reared up again with the advent of user-friendly mechanical and aspiration thrombectomy technologies. This is especially true for submassive PE, which is an area for potential growth both for understanding the pathophysiology of the disease process and management. Multiple devices are available for treatment of PE. Understanding the risks and benefits of each device is paramount in the complex management of PE.
Keywords: pulmonary embolism; thrombectomy; catheter-directed thrombolysis; ultrasound; EKOS; Inari